2018
DOI: 10.1016/j.foodres.2017.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene-rich extract from red guava ( Psidium guajava L.) displays cytotoxic effect against human breast adenocarcinoma cell line MCF-7 via an apoptotic-like pathway

Abstract: This study investigated a lycopene-rich extract from red guava (LEG) for its chemical composition using spectrophotometry, mass spectrometry, attenuated total reflectance-fourier transform infrared spectroscopy (ATR-FTIR), and computational studies. The cytotoxic activity of LEG and the underlying mechanism was studied in human breast adenocarcinoma cells (MCF-7), murine fibroblast cells (NIH-3T3), BALB/c murine peritoneal macrophages, and sheep blood erythrocytes by evaluating the cell viability with 3-(4,5-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 58 publications
2
30
1
1
Order By: Relevance
“…Here we have shown that extracts from red guava fruit can induce cell death in TNBC cells. Most studies have shown that guava extracts induce large amounts of apoptotic death in various cancer cells [7,22,31]. Our study, in contrast, found that red guava extracts induce apoptotic and necrotic cell death in TNBC.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Here we have shown that extracts from red guava fruit can induce cell death in TNBC cells. Most studies have shown that guava extracts induce large amounts of apoptotic death in various cancer cells [7,22,31]. Our study, in contrast, found that red guava extracts induce apoptotic and necrotic cell death in TNBC.…”
Section: Discussioncontrasting
confidence: 79%
“…A previous study showed that extracts purified from guava fruit do not have anti-cancer activity in breast cancer cells [21]. However, extracts obtained from lycopene-rich red guava fruit can inhibit ER-positive breast cancer growth [22]. Here we also found that extracts purified from red guava fruit can inhibit TNBC growth, with LMW extracts and total extracts having similar cytotoxic effects on these cells.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The antioxidant property is responsible for its beneficial effects on human health. 31 Pitanga 1 presented the highest content for this carotenoid with 0.1876 g kg −1 (0.029 g kg −1 fw). This fruit presented higher levels than papaya (0.022 g kg −1 fw) 28 and exhibited lower content than watermelon and tomatoes.…”
Section: Resultsmentioning
confidence: 94%
“…Lycopene is a powerful antioxidant carotenoid, and its potent antioxidant activity of lycopene is generally responsible for the protection of cellular systems from a variety of reactive oxygen‐nitrogen species. The antioxidant property is responsible for its beneficial effects on human health . Pitanga 1 presented the highest content for this carotenoid with 0.1876 g kg −1 (0.029 g kg −1 fw).…”
Section: Resultsmentioning
confidence: 99%